Self-care among breast cancer survivors: A concept analysis - Lina Anisa Nasution; Yati Afiyanti (Jurnal Keperawatan Padjadjaran, 2024)
Background: Breast cancer survivors have an excellent prognosis and a high survival rate, thus each survivor requires self-care abilities throughout their complex therapy. The concept of self-care is not a new concept in the nursing field, but it is necessary to analyze it as there are still inconsistencies in its use and unclear definitions, especially in the context of breast cancer survivors. Purpose: The purpose of this study was to describe the concept of self-care among breast cancer survivors by employing the Walker and Avant’s analysis method. Methods: The Walker and Avant’s concept analysis method comprises of eight systematic steps. The literature search was conducted through electronic databases, such as ScienceDirect, MEDLINE, EBSCO, ProQuest and SAGE, with the search constraints ranging from 2003 to 2023. Results: The literature search identified 115 articles in the fields of medicine, nursing, sociology, psychology, economics, anthropology, pharmacy, computer science and midwifery. Following the analysis, 30 articles were selected for this study. The concept of self-care was defined as: 1) survivor activity; 2) survivor awareness; 3) self-management; 4) prevention of morbidity and recurrence; 5) improved health. Meanwhile, the concept’s antecedents included self-efficacy, self-care agency and social support, and the consequences included symptom control, improved coping, improved well-being, and improved quality of life. Conclusions: Understanding the attributes of self-care among breast cancer survivors along with their antecedents and consequences could facilitate its development in nursing practices. The self-care concept is utilized for self-care assessment and implementation of appropriate interventions in the context of breast cancer survivors who have completed the therapy.